Evidence-based nutritional strategies to enhance athletic performance - Schroeder, N. (Strength and Conditioning Journal, 2022)
In today`s digital era, nutritional information, and misinformation, is readily available for most people by media outlets, social media, and on-line streaming videos. Nutrition is of utmost interest because of its role in health, fitness, weight management, and athletic performance. Because of the public interest and information availability, qualified health care providers and exercise professionals can be an excellent source of evidence-based nutrition counseling for appropriate clients to improve overall health and athletic performance. The goal of this article is to provide a source of practitioner and client evidence-based education regarding nutritional strategies to improve athletic performance.